#### • Class 11 Physics Demo

Explore Related Concepts

#### • calculator that shows work

Question:Example: Cell A1 = 4:00 AM. I'd like Cell A2 to show 8:00 PM (that's cell "A1-8" hours). I'd like Cell A3 to show 12:00 AM (that's cell A1-4 hours). How do I set up the formula's in cells A2 and A3? Note: the formula =TIME(HOUR(A1)+16, MINUTE(A1), SECOND(A1)) results in a #VALUE! error excelerate and Ted Pack - my thanks to both. excelerate you were the first correct answer; but I goofed in applying your first answer.

Answers:TIME(HOUR(A1)+16, MINUTE(A1), SECOND(A1)) worked fine for me when I had A1 as ="04:00" (Note the equal sign and quotation marks.)

Question:Using a balance scale and weights of 1kg, 3kg, 9kg, and 27kg, how many objects of different weights can be weighed? The objects to be weighed and the wights may be placed in either pan of the balance scale. (show work) Make sure to answer all parts of question. When someone gets the answer right and shows work i will post the correct answer and select best answer. HAVE FUN

Answers:1 2(3-1) 3 4(3+1) 5(9-3-1) 6(9-3) 7(9+1-3) 8(9-1) 9 10(9+1) 11(9+3-1) 12(9+3) 13(9+3+1) 14(27-9-3-1) 15(27-9-3) 16(27+1-9-3) 17(27-9-1) 18(27-9) 19(27+1-9) 20(27+3-1-9) 21(27+3-9) 22(27+3+1-9) 23(27-3-1) 24(27-3) 25(27+1-3) 26(27-1) 27 28->40 add 27 to the instructions for 1->13 a minus sign means put the weight in the same pan as the object being measured. You can weigh 40 different weights, or 41 if you include 0kg

Question:1. 54+2 24- 6 2. 5 27-2 90+ 40- 48

Answers:1) 54 + 2 24 - 6 = (3^2 * 6) + 2 (2^2 * 6) - 6 = 3 6 + 2(2) 6 - 6 = 3 6 + 4 6 - 6 = 7 6 - 6 = 6 6 2) 5 27 - 2 90 + 40 - 48 = 5 (3^2 * 3) - 2 (3^2 * 10) + (2^2 * 10) - (4^2 * 3) = 5(3) 3 - 2(3) 10 + 2 10 - 4 3 = 15 3 - 6 10 + 2 10 - 4 3 = 15 3 - 4 3 - 4 10 = 11 3 - 4 10

Question:whats the answer if you subtract the two functions, can you also show how it is worked out thanks x+ 2y ______ x^2 + 4xy +4y^2 minus 2x ___ x^2 -4y^2

Answers:1. factorise everything (x+ 2y) / (x^2 + 4xy +4y^2) - (2x) / (x^2 -4y^2) = (x+ 2y) / (x + 2y)(x +2y) - (2x) / (x - 2y)(x + 2y) in this case simplify the first term = 1/(x +2y) - (2x) / (x - 2y)(x + 2y) multiply the first term by (x - 2y) to make a common denominator =(x - 2y)/(x - 2y)(x +2y) - (2x) / (x - 2y)(x + 2y) now subtract the numerators =[(x - 2y) - (2x)] / (x - 2y)(x + 2y) =[ -x - 2y] / (x - 2y)(x + 2y) = - ( x+ 2y) / (x - 2y)(x + 2y) divide the common factor = -1 / (x - 2y) hope that helps Good Luck!